Common fixed point theorems for firmly nonspreading mappings and quasi-nonexpansive mappings in CAT(0) spaces - Tanaphong Prommai (2020)
© 2020 by the Mathematical Association of Thailand. In this paper, we prove the existence of a common fixed point for firmly nonspreading mappings and quasi-nonexpansive mappings in CAT(0) spaces. Using the concept of Ishikawa iterative scheme, we define the sequence {xn} by (Formula Presented) for all n ε N, where E is a nonempty closed and convex subset of a complete CAT(0) space, S and T are mappings defined on E. We prove that the sequence {xn} δ - converges to a common fixed point for firmly nonspreading mappings and quasi-nonexpansive mappings in CAT(0) spaces.